Convergence of Depth from Texture and Depth from Disparity in Macaque Inferior Temporal Cortex - Liu, Yan (J Neurosci, 2004)
The visual system must reconstruct the three-dimensional structure of an object from two-dimensional retinal images. Previous research has shown that macaque inferior temporal (IT) neurons, although belonging to the ventral visual stream, code for depth defined by binocular disparity gradients. Here, we demonstrate that macaque IT neurons also code for depth defined by texture gradients, a monocular depth cue. Single IT neurons were selective for the tilt of texture-defined surfaces, and the tilt preferences of individual neurons remained the same, whether surfaces were defined by texture or disparity cues. Furthermore, the tilt preference was invariant over different types of textures and slants, suggesting an abstract representation of surface tilt in ventral visual cortex.